Girl who kicked the hornet's nest [videorecording (DVD)] = Luftslottet som sprängdes - Alfredson, Daniel, 1959-; Nyqvist, Michael, 1960-2017; Rapace, Noomi, 1979-; Endre, Lena, 1955-; Larsson, Stieg, 1954-2004 (Music Box Films, 2010)
The final installment of Stieg Larsson's 'Millennium' trilogy. Lisbeth Salander is fighting for her life in more ways than one. In an intensive care unit and charged with three murders, she will have to not only prove her innocence, but also identify and denounce the same corrupt government institutions that nearly destroyed her life. Once upon a time, she was a victim. Now, Lisbeth Salander is fighting back.